THE MORPHOLOGICAL REACTION OF LIVER AND SPLEEN TO THE BACTERIAL INTOXICATION IN EXPERIMENTAL SEPSIS - Dgebuadze, M.A. (World of Medicine and Biology, 2015)
Experiments were carried out on 15 mature Chinchila rabbits of both sexes with sepsis caused by staphylococcus aureus. On 9th and10th days after bacterial contamination morphological study of liver and spleen of the rabbits were conducted using histological and morphometric methods. Thrombohemorrhagic disorders of vessels and parenchyma of the liver and spleen were revealed, wich were followed by dystrophic-necrotic changes of parenchyma abovementioned organs.
Keywords: experimental sepsis; liver; spleen